2017
DOI: 10.20546/ijcrbp.2017.411.009
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Plant Steroids and their Biological Activities

Abstract: A b s t r a c t A r t i c l e I n f oThe present review describes the biological activities of natural plant chlorinated steroids. About forty biologically active chlorinated steroids have shown confirmed cytostatic, antineoplastic, anti-eczematic, antidiabetic, antibacterial, and other activities. The structures and reported and predicted activities of chlorinated steroids are available. With the computer programme PASS and based on structure-activity relationships (SAR), some additional activities are also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The distribution of biological activity percentages for aragusterol C is depicted in Figure 33. Another compound, aragusteroketal C (157), which is a steroid with a dimethylketal structure, was also isolated from the same sponge. This chlorinated steroid displayed cytotoxic activity against the KB tumor cell line, with an IC 50 value of 4 ng/mL [191].…”
Section: Halogenated Steroids Derived From Marine Sourcesmentioning
confidence: 97%
“…The distribution of biological activity percentages for aragusterol C is depicted in Figure 33. Another compound, aragusteroketal C (157), which is a steroid with a dimethylketal structure, was also isolated from the same sponge. This chlorinated steroid displayed cytotoxic activity against the KB tumor cell line, with an IC 50 value of 4 ng/mL [191].…”
Section: Halogenated Steroids Derived From Marine Sourcesmentioning
confidence: 97%
“…A small number of chlorinated withanolides have previously been encountered in plants of Solanaceae as minor metabolites and many of these occur as 5,6-chlorohydrins containing 5α-chloro-6β-hydroxy substituents [25,[44][45][46][47][48]. It has been suggested that the chlorine atom present in these 5,6-chlorohydrins may originate from NaCl present in the plant [2].…”
Section: Isolation and Structure Elucidationmentioning
confidence: 99%
“…The Madagascan sponge Amphimedon sp. contains amphimedonoic acid (66) and psammaplysene E (67), along with the known 3,5-dibromo-4-methoxybenzoic acid. 29 Neither compound is active against human epidermoid carcinoma KB cells (IC 50 > 10 µg/mL).…”
Section: Spongesmentioning
confidence: 99%
“…An excellent review of chlorinated plant steroids and their biological activities has appeared. 66 A series of steroidal withanolides, including eleven new examples and two known chlorine-containing ones, were isolated from the plant Physalis peruviana L. (Solanaceae), and were evaluated for their cytotoxicity against prostate and renal cancer cells. 67 The two known chlorinated examples (not shown) physalolactone and 4-deoxyphysalolactone 2 are inactive.…”
Section: Terrestrial Plantsmentioning
confidence: 99%